Answer:
<SDQ
Step-by-step explanation:
Eg if a = b, b = c, then a = c
Answer:
-8/7
Step-by-step explanation:
13-7. 8
--------- = --
7
7
Answer:
Hey Dude ok so it's g = 7 Have a nice day!
Step-by-step explanation:Simplifying
-2 = g + -9
Reorder the terms:
-2 = -9 + g
Solving
-2 = -9 + g
Solving for variable 'g'.
Move all terms containing g to the left, all other terms to the right.
Add '-1g' to each side of the equation.
-2 + -1g = -9 + g + -1g
Combine like terms: g + -1g = 0
-2 + -1g = -9 + 0
-2 + -1g = -9
Add '2' to each side of the equation.
-2 + 2 + -1g = -9 + 2
Combine like terms: -2 + 2 = 0
0 + -1g = -9 + 2
-1g = -9 + 2
Combine like terms: -9 + 2 = -7
-1g = -7
Divide each side by '-1'.
g = 7
Simplifying
g = 7
Answer:
10ˣ² +19ˣ + 6
Step-by-step explanation:
5ˣ(2x + 3) + 2 (2x + 3 )
10x² + 15x + 2(2x + 3 )
10x² + 15x + 4x + 6
= 10x² + 19x + 6
Answer:
x = 3
Step-by-step explanation:
7 (1/3.5) = 2
6 (1/2) = 3